2021
DOI: 10.3389/fimmu.2021.639049
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Modulates the Proinflammatory Memory-Like Response of Microglia Induced by BAFF

Abstract: BackgroundRecently trained immunity of microglia provided an opportunity to study the chronic effect of microglial activation and its metabolic rewiring in neuroimmunological diseases. Since elevated levels of B cell-activating factor (BAFF) have been proved to be associated with some chronic neuroimmunological disorders. Here, we used the trained innate immunity model to analyze the effect of BAFF, a vital regulator of the adaptive immune system, on long-term microglial activation and metabolic reprogramming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
1
15
0
Order By: Relevance
“…5A). BAFF belongs to the TNF family and plays a vital role in the survival of B-lymphocytes (15). We confirmed that PMN-MDSCs from CIA mice expressed higher levels of BAFF than those from DBA/1J mice (Fig.…”
Section: Pmn-mdscs Modulated B Cells Via Baffsupporting
confidence: 76%
“…5A). BAFF belongs to the TNF family and plays a vital role in the survival of B-lymphocytes (15). We confirmed that PMN-MDSCs from CIA mice expressed higher levels of BAFF than those from DBA/1J mice (Fig.…”
Section: Pmn-mdscs Modulated B Cells Via Baffsupporting
confidence: 76%
“… 115 Similar to experimental models of trained immunity, 4 weeks after infection of mice with Salmonella typhimurium , microglia had greater immune reactivity and exaggerated local inflammatory responses to subsequent stimulation with LPS. 116 Recently, rapamycin was shown to suppress the trained immunity‐like responses of microglia through targeting the mTOR/HIF‐1α signaling pathway, 117 providing novel insights into current therapeutic strategies in neurodegenerative diseases.…”
Section: The Yin‐yang Balance Of Trained Immunitymentioning
confidence: 99%
“…After incubation, the medium was removed and the cells were washed with PBS (0.01 M, pH 7.40) before further studies. BV2 cells were pretreated with 100 nM rapamycin and 1 mM DMOG for 1 h before Hb incubation [23,24].…”
Section: Drug Administrationmentioning
confidence: 99%